Kualitas Argumentasi Mahasiswa dalam Wacana Debat “Budaya Literasi Sekolah” pada Pembelajaran Keterampilan Berbahasa - Lupita Sari Pitra Wardani; Atiqa Sabardila (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2020)
The purpose of this study is to analyze the method in the debate of “school literacy culture” conducted by postgraduate students of the Muhammadiyah University of Surakarta in language skills learning. The data of this study are words and sentences in the orthographic transcriptional results of the “school literacy culture” debate. The data source is the result of a debate from a graduate student at the Muhammadiyah University of Surakarta under the title “culture of school literacy”. The method used in this research is a qualitative descriptive approach. Data collection used the record method and continued with the note taking technique. Data analysis used the referential equivalent method and was strengthened by the intralingual method. The results of this study are the method of analysis in the discussion begins with an interesting opening, then the statement delivered by the debate participants in accordance with the debate theme, the debate participants' thinking lines are clear and coherent, the priority scale has been fulfilled, the time allocation is appropriate, and the closing submission has been cover the whole idea. The conclusion from this research is that the debate has been going well but there are still parties who dominate